Representasi Konflik Sosial dalam Novel Kami (Bukan) Generasi Bacot Karya J.S. Khairen - Fajriah, Sarah; Nasution , Muhammad Ismail (Persona: Kajian Bahasa dan Sastra, 2023)
One of the problems that is often raised in a novel is social conflict. The social conflict contained in a work is one of the interests for readers to enjoy the conflict presented in the literary work. Apart from being enjoyed, this is also an attraction for literary works to be studied. To understand the social conflict contained in a literary work, researchers must understand the character of the characters in the literary work. This research aims to describe the forms, causes and impacts of the representation of social conflict in the novel Kami (bukan) Generasi Bacot by J.S. Khairen. This type of research is literary research with descriptive methods. The data in this research are words, phrases, clauses and sentences that refer to the social conflict contained in the novel Kami (Not) Generasi Bacot by J.S. Khairen. Based on the research results, three forms of social conflict were found, four causes of social conflict, and three impacts of social conflict. The conclusion of this research is from the results of the analysis and interpretation of data in the novel Kami (bukan) Generasi Bacot by J.S. Khairen found 40 pieces of data related to social conflict.